Analyzing the Efforts of Digitizing Cultural Heritage in Vietnam and Its Role in Preserving Indigenous Knowledge, Promoting Education, and Tourism - Duc, Tran Minh; Tien, Nguyen Van (Journal of Posthumanism, 2025)
This article aims to analyze the efforts of digitizing cultural heritage in Vietnam in the context of a rapidly progressing global digital transformation. The study focuses on three key aspects: the role of digitization in preserving and disseminating indigenous knowledge; its contributions to education—particularly in creating culturally rich learning materials; and its potential to promote sustainable tourism through innovative experiences such as virtual museums, digital cultural maps, and virtual reality applications. The primary research method employed is literature review, analyzing academic works and practical reports on cultural heritage digitization in Vietnam. Additionally, the article examines several case studies, such as the “Digitization of Van Mieu – Quoc Tu Giam” project, the “Vietnam Digital Museum,” and various initiatives for digitizing intangible heritage in the Central Highlands. From these cases, the study draws insights into the effectiveness, limitations, and future potential of these digitization efforts. Preliminary findings show that digital technologies are positively contributing to the governance of cultural heritage—not only in terms of data storage but also by expanding access, interaction, and the dissemination of cultural values within communities. If systematically implemented with interdisciplinary collaboration, these efforts will serve as a crucial foundation for preserving national cultural identity, enhancing educational quality, and promoting Vietnam’s tourism image in the digital age.